Plant Lectins as Insecticidal Agents Against Cotton Leafworm Spodoptera littoralis and Their Potential Applications in Crop Protection - Mohsen, Soad F.E.; Abbassy, Moustafa A.; Abou-Taleb, Hamdy K; Rabea, Entsar I. (Natural Products Journal, The, 2021)
Background: The production of insecticidal proteins is one of the greatest vital direct defense responses in plants against the attack by phytophagous insects. One particular class of the entomotoxic proteins present in many plant species is lectins that is used against a wide range of important insects. Aim: The insecticidal activity of two lectins from seeds of white kidney bean (Phaseolus vulgaris) and soybean (Glycine max) on the growth, development and survival of the cotton leafworm, Spodoptera littoralis Boisd. (Lepidoptera: Noctuidae) was studied. Methods: Lectin products were isolated and purified using ammonium sulfate precipitation. Insecticidal activity, growth-inhibitory and physiological effects on the differential haemocyte count of lectin products were evaluated against S. littoralis. In vivo effects of lectin products on some S. littoralis enzymes were also determined. Results: Lectin contents in 250 g seeds were 700 and 500 mg in soybean and white kidney bean, respectively. The total protein concentrations were 160-163 and 118-120 mg/mL in soybean and white kidney bean, respectively. The insecticidal activity of lectin products exerted a strong effect on the larval weight gain and the reduction of the weight reached to 75.25%. Furthermore, the other developmental stages of pupation and adult formation were also affected. An elongated larval duration was noticed since larval duration was 24.8 days compared with control (12.0 days). Complete pupation (100%) was recorded in the control; however, a significant decrease in pupation was found to be 54.0% in treated larvae. Lectin products increased the average number of 123.9 haemocytes (123.9) compared to the control (94.4 haemocytes/field). In addition, lectin products inhibited the activity of total proteases, α-amylase, GST and total esterases. Conclusion: It can be concluded that the lectins have high potential in pest control strategies based on their activity towards the cotton leafworm, S. littoralis. These findings suggest that lectin products are interesting tools for integrated pest management in important agriculture crops.
Keywords: pupation